Managing ethnicity and constructing the 'Bangsa Malaysia' (A United Malaysian Nation) - Ishak, Mohamed Mustafa (Universiti Utara Malaysia, 2002)

(untitled)
The question of nation-building has always been a central issue in Malaysian politics. Whilst the country has been able to sustain stable politics since the 1969 racial tragedy, spawning two decades rapid socio-economic development until the 1997 Asian economic crisis, the project of nation-building remained a basic national agenda yet to be fully resolved. This short paper investigates the delicate process of nation-building in Malaysia in the post 1970s, especially in the context of the vision of constructing the Bangsa Malaysia or united Malaysian nation enshrined in Mahathir's Vision 2020 project which was introduced in 1991. The aim of the paper is firstly, to highlight the underlying socio-political parameters that shaped and influenced the politics of nation-building in the country, and secondly, to explore the viability of the project of Bangsa Malaysia in the context of the daunting challenges involved in the process of nation-building. The paper contends that, based on the Malaysian experience, the potent interplay between the forces of ethnicity and nationalism constitute the crux of the problem in the politics of nation-building in Malaysia. This dialectic it is argued, stems from the prevalence of the varying 'nationalisms' within and across ethnic groups. These phenomena have not only shaped the pattern of ethnic political mobilization in the countv, but above all, laid the most complex set of obstacles in the path of the project of nation-building. The paper argues that the project of constructing the Bangsa Malaysia therefore, can be seen as significant attempt by the state to reconcile the competing 'nationalism'. It can also be considered as an attempt to consolidate Malay nationalism and cultural pluralism, thus promoting the development of 'civic nationalism' or creation of a 'supra-ethnic' national identity. The 'nation', therefore, is depicted as a 'mosaic of cultures', but with a strong fervour of Malay nationalism. However, the viability of the envisaged project is yet to be tested. The concept itself is still vague to many people and the challenges ahead are enormous, involving political, economic, socio-cultural and religious issues. Indeed the project risks becoming the 'latest' in the series of competing notions of 'nation-of-intent' circulating in Malaysia. The paper contends that whilst, to some extent, the socio-political landscape of Malaysian society has been rapidly changing, especially in the past two decades of Mahathir's reign, ethnicity still pervades Malaysian political life. The paper probably difers from many previous studies on nation-building in Malaysia, which have mainly focused on either the historical dimensions or those which have examined the impact of key national policies. It is hoped that this brief paper would be able to contribute towards broadening the perspective in the analysis of ethnic relations and nation-building in Malaysia, thus, deepening the understanding of Malaysia politics and society.